2013
DOI: 10.3791/50631
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Recording, Sensory Field Mapping, and Culturing Identified Neurons in the Leech, <i>Hirudo medicinalis</i>

Abstract: The freshwater leech, Hirudo medicinalis, is a versatile model organism that has been used to address scientific questions in the fields of neurophysiology, neuroethology, and developmental biology. The goal of this report is to consolidate experimental techniques from the leech system into a single article that will be of use to physiologists with expertise in other nervous system preparations, or to biology students with little or no electrophysiology experience. We demonstrate how to dissect the leech for r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…It enable us to use the neu rons of mollusks as eligible models [9][10][11][12][13][14][15][16][17][18], in paral lel with the neurons of warmblooded animals, for experimental research on the performance of the ion channels and the mechanisms of influences on them made by various physical factors, chemical substanc es and pharmaceutical drugs either of already known nature or being designed. Our studies were carried out on the large identified (100-200 µm) neurons of the parietal ganglia (LPaG and RPaG) ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…It enable us to use the neu rons of mollusks as eligible models [9][10][11][12][13][14][15][16][17][18], in paral lel with the neurons of warmblooded animals, for experimental research on the performance of the ion channels and the mechanisms of influences on them made by various physical factors, chemical substanc es and pharmaceutical drugs either of already known nature or being designed. Our studies were carried out on the large identified (100-200 µm) neurons of the parietal ganglia (LPaG and RPaG) ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…This invertebrate model can generate a broad range of behaviors [25] , [26] , but possesses a simple nervous system that can be easily accessed to extract individual ganglia, the anatomical organization of which is highly conserved across specimens [27] . Neurons within a ganglion are functionally characterized and identifiable by their position, size, and electrophysiological profile [28] , [29] , and offer very reliable responses to EL stimulation. Finally, it is possible to record viable neural responses from an isolated ganglion for extended periods of time [29] .…”
Section: Introductionmentioning
confidence: 99%
“…Neurons within a ganglion are functionally characterized and identifiable by their position, size, and electrophysiological profile [28] , [29] , and offer very reliable responses to EL stimulation. Finally, it is possible to record viable neural responses from an isolated ganglion for extended periods of time [29] .…”
Section: Introductionmentioning
confidence: 99%
“…Leeches were anesthetized on ice for 30 min before dissection and were pinned, dorsal side up, to a layer of Sylgard on the bottom of the dissection chamber. Dissection was made according to an established procedure (Titlow et al, 2013). Briefly, a longitudinal cut was made through skin and muscle layers along the dorsal midline of the leech to expose the nerve cord and segmental ganglia.…”
Section: Animals and Dissectionmentioning
confidence: 99%